Advancing Android Privacy Assessments with Automation - Khedkar, Mugdha; Schlichtig, Michael; Bodden, Eric (In Proceedings of the 39th IEEE/ACM International Conference on Automated Software Engineering Workshops (ASEW ’24))
Android apps collecting data from users must comply with legal frameworks to ensure data protection. This requirement has become even more important since the implementation of the General Data Protection Regulation (GDPR) by the European Union in 2018. Moreover, with the proposed Cyber Resilience Act on the horizon, stakeholders will soon need to assess software against even more stringent security and privacy standards. Effective privacy assessments require collaboration among groups with diverse expertise to function effectively as a cohesive unit. This paper motivates the need for an automated approach that enhances understanding of data protection in Android apps and improves communication between the various parties involved in privacy assessments. We propose the Assessor View, a tool designed to bridge the knowledge gap between these parties, facilitating more effective privacy assessments of Android applications.

Die Mediävistik und ihr Mittelalter

Die Mediävistik und ihr Mittelalter. Einleitung - Mersch, Katharina Ulrike; de Boer, Jan-Hendryk; Bubert, Marcel (Die Mediävistik und ihr Mittelalter)

Brown, Warren: Beyond the Monastery Walls. 2023, xiv, 385 S.: Illustrationen, Karten. - ISBN 978-1-108-47958-5 - Mersch, Katharina Ulrike (Deutsches Archiv für Erforschung des Mittelalters)

Serial hot gas welding - Heating and welding behaviour of a slot nozzle - Albrecht, Mirko; Bialaschik, Max Oliver; Gehde, Michael; Schöppner, Volker (AIP Conference Proceedings)

Geschichtskulturen im digitalen Wandel?

Digitale Interpretationsedition und Filmmusikedition als multimodale Schwestern – Gemeinsame Herausforderungen und Lösungsansätze - Berndt, Axel; Münzmay, Andreas

OPEN FAUST Preview (dataset) - Bachmann, Tobias; Frömmel, Lena; Münzmay, Andreas
Peter Joseph von Lindpaintner: Ouverture, Entreacte, Chöre und Lieder zu Goethes Faust nach der szenischen Einrichtung von Carl Seydelmann. Historical-Critical Digital Edition by Tobias Bachmann, Lena Frömmel and Andreas Münzmay. The dataset, consisting of TEI and MEI files, is the historical-critical digital edition. The data structure allows for visualization via EDIROM ONLINE.

Multi-Modal Data Networks in Music: Thoughts on a Digital Performance Edition - Berndt, Axel; Münzmay, Andreas; Bömcke-Vollmer, Frithjof (DAGA 2024 – 50. Jahrestagung für Akustik)

On the Effectiveness of Heterogeneous Ensemble Methods for Re-identification - Klüttermann, Simon; Rutinowski, Jérôme; Polachowski, Frederik; Nguyen, Anh; Grimme, Britta; Roidl, Moritz; Müller, Emmanuel (2024 International Conference on Machine Learning and Applications (ICMLA))

Mikromechanische Analyse von Eigenspannungen in direktgefügten kohlenstofffaserverstärkten Kunststoff-Stahl-Schichtverbunden - Tinkloh, Steffen Rainer
Residual stresses in directly joined laminates made of steel and carbon fiber reinforced epoxy resin reduce the interface and bond strength and thus have to be taken into account for the strength analysis of structural components. For a holistic description of residual stresses, a thermo-chemo-mechanical constitutive model is introduced in the present work and presented for the multi-scale analysis of residual stress patterns. In this context, the analysis of representative unit cells with regular and stochastic distribution of fibers gives information about the associated deformation and stress fields. Dehomogenization at macroscopically highly stressed regions, characterized by local stress peaks, reveals the effect of gradient deformation in the microstructure. Another aspect of this work is the development of FFT-based Galerkin methods, which allows an evaluation of the effect of defect densities, heterogeneities and morphologies on the applicability of the incremental hole drilling method. It could be demonstrated that the incremental hole drilling method is particularly sensitive to defects running along the surface.
Keywords: Hybride Werkstoffverbunde; Eigenspanungen; FFT-basierte Galerkin-Methode; Mikromechanik; Finite-Elemente-Methode

Effect of Substrate Temperature on Bead Track Geometry of 316L in Directed Energy Deposition: Investigation and Regression Modeling - Chalicheemalapalli Jayasankar, Deviprasad; Gnaase, Stefan; Lehnert, Dennis; Walter, Artur; Rohling, Robin; Tröster, Thomas (Metals)
The optimization of process parameters in powder Directed Energy Deposition (DED) is essential for achieving consistent, high-quality bead geometries, which directly influence the performance and structural integrity of fabricated components. As a subset of additive manufacturing (AM), the DED process, also referred to as laser metal deposition (LMD), enables precise, layer-by-layer material deposition, making it highly suitable for complex geometries and part repair applications. Critical parameters, such as the laser power, feed rate, powder mass flow, and substrate temperature govern the deposition process, impacting the bead height, width, contact angle, and dilution. Inconsistent control over these variables can lead to defects, such as poor bonding, dimensional inaccuracies, and material weaknesses, ultimately compromising the final product. This paper investigates the effects of various process parameters, specifically the substrate temperature, on bead track geometry in DED processes for stainless steel (1.4404). A specialized experimental setup, integrated within a DED machine, facilitates the controlled thermal conditioning of sample sheets. Using Design of Experiments (DoE) methods, individual bead marks are generated and analyzed to assess geometric characteristics. Regression models, including both linear and quadratic approaches, are constructed to predict machine parameters for achieving the desired bead geometry at different substrate temperatures. Validation experiments confirm the accuracy and reliability of the models, particularly in predicting the bead height, bead width, and contact angle across a broad range of substrate temperatures. However, the models demonstrated limitations in accurately predicting dilution, indicating the need for further refinement. Despite some deviations in measured values, successful fabrication is achieved, demonstrating robust bonding between the bead and substrate. The developed models offer insights into optimizing DED process parameters to achieve desired bead characteristics, advancing the precision and reliability of additive manufacturing technology. Future work will focus on refining the regression models to improve predictions, particularly for dilution, and further investigate non-linear interactions between process variables.
Keywords: additive manufacturing; direct energy deposition; laser metal deposition

Advancements in Hybrid Additive Manufacturing: Integrating SLM and LMD for High-Performance Applications - Chalicheemalapalli Jayasankar, Deviprasad; Gnaase, Stefan; Kaiser, Maximilian Alexander; Lehnert, Dennis; Tröster, Thomas (Metals)
Additive manufacturing (AM) technologies enable near-net-shape designs and demand-oriented material usage, which significantly minimizes waste. This points to a substantial opportunity for further optimization in material savings and process design. The current study delves into the advancement of sustainable manufacturing practices in the automotive industry, emphasizing the crucial role of lightweight construction concepts and AM technologies in enhancing resource efficiency and reducing greenhouse gas emissions. By exploring the integration of novel AM techniques such as selective laser melting (SLM) and laser metal deposition (LMD), the study aims to overcome existing limitations like slow build-up rates and limited component resolution. The study’s core objective revolves around the development and validation of a continuous process chain that synergizes different AM routes. In the current study, the continuous process chain for DMG MORI Lasertec 65 3D’s LMD system and the DMG MORI Lasertec 30 3D’s was demonstrated using 316L and 1.2709 steel materials. This integrated approach is designed to significantly curtail process times and minimize component costs, thus suggesting an industry-oriented process chain for future manufacturing paradigms. Additionally, the research investigates the production and material behavior of components under varying manufacturing processes, material combinations, and boundary layer materials. The culmination of this study is the validation of the proposed process route through a technology demonstrator, assessing its scalability and setting a benchmark for resource-efficient manufacturing in the automotive sector.
Keywords: additive manufacturing (AM); selective laser melting (SLM); laser metal deposition (LMD); hybrid manufacturing; process optimization; 316L; 1.2709

Development of a Tool Concept for Prestressed Fibre Metal Laminates and Their Effect on Interface Failure - Irmak, Hayrettin; Tinkloh, Steffen Rainer; Marten, Thorsten; Tröster, Thomas (Journal of Composites Science)
The use of hybrid materials as a combination of fibre-reinforced plastic (FRP) and metal is of great interest in order to meet the increasing demands for sustainability, efficiency, and emission reduction based on the principle of lightweight design. These two components can therefore be joined using the intrinsic joining technique, which is formed by curing the matrix of the FRP component. In this study, for the hybrid joint, unidirectionally pre-impregnated semi-finished products (prepregs) with duromer matrix resin and micro-alloyed HC340LA steel were used. In order to conduct a detailed investigation, the damage mechanisms of intrinsically produced fibre metal laminates (FMLs), a new clamping device, and a novel pressing tool were designed and put into operation. The prepregs were prestressed by applying a preloading force using a specially designed prestressing frame. Hybrid specimens were then produced and subjected to nanoindentation and a shear tensile test. In particular, the effect of the residual stress state by varying the defined prestressing force on the damage mechanisms was studied. The results showed that no fracture patterns occurred in the interface of the specimens without preloading as a result of curing at 120 °C, whereas specimens with preloading failed at the boundary layer in the tensile range. Nevertheless, all specimens cured at 160 °C failed at the boundary layer in the tensile range. Furthermore, it was proven that the force and displacement of the preloaded specimens were promisingly higher than those of the unpreloaded specimens.
Keywords: CFRP; prestressing; fibre metal laminate; interface; prepreg; shear tensile test

Experimental investigations on anvil-free ultrasonic welding for welding situations with one sided access - Schöppner, Volker; Arndt, Theresa

Entwicklung einer analytischen Berechnungsmethode zur Auslegung thermoplastischer Flanschsysteme
Inhalt Aktuelle rechtliche Rahmenbedingungen TA Luft – Wesentliche Änderungen, Herausforderungen, Konsequenzen in der Praxis und laufende Aktivitäten 1 Die Lösungsmittelbilanz bei VOC Anlagen als Nachweis der Einhaltung des Grenzwertes für diffuse Emissionen The solvent mass balance for VOC installations as verification of compliance with the limit value for fugitive emissions 11 Diffuse Emissionen Dichte Flanschverbindungen – Richtlinie VDI 2290 23 Technik zur Vermeidung und Verminderung von diffusen Emissionen – Regel- und Absperrarmaturen 37 Erstellung der Lösungsmittelbilanz im Kontext der 31. BImSchV – Rechtliche Anforderungen, praktische Herausforderungen und Unsicherheiten Preparation of the solvent balance in the context of the 31. BImSchV - legal requirements, practical challenges and uncertainties 45 Entwicklung einer analytischen Berechnungsmethode zur Auslegung thermoplastischer Flanschsysteme 61 VKA Control - Bewertung von Legionellenemissionen aus Verdunstungskühlanlagen: Neue Erkenntnisse und Methoden 71 Verbrennungsführung und Minderung organischer Emissionen 27. BImSchV versus Klimaschut...

Development of an analytical calculation method for the design of thermoplastic flange systems - Bartmann, Finn; Riedl, Alexander; Moritzer, Elmar (22nd International Sealing Conference 2024)
"In the course of environmental protection and the amendment of TA Luft, emissions from flange connections must be reduced (to L0.01). The design and calculation of steel flanges is easy to handle with the help of EN 1591-1 and EN 13555. However, these standards are not suitable in their current form for thermoplastic sealing joints, such as those used in natural gas supply. For this reason, lengthy and cost-intensive tests must currently be carried out to verify tightness and strength. The aim of a doctoral project is to develop a time-efficient and cost-effective analytical calculation method based on the existing standards. For this purpose, the energy-elastic material parameters of the steel must be replaced by elastoplastic material parameters of the thermoplastics and the calculation algorithm adapted accordingly. The problem is to be investigated with the aid of numerical structural simulations (FEM) and experimental tests."

Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian (DVS Plenarsitzung AG W4 Fügen von Kunststoffen)

Vielfalt begrüßen. Ein rassismuskritischer Blick auf Jesus-Darstellungen in christlicher Kunst und Kinderbibeln - Keuchen, Marion; Lerke, Stephanie (Die Bibel in der Kunst/ Bible in the Arts)
Despite increasing ethnic diversity in Germany, racist structures are still deeply rooted in society, as is demonstrated by various initiatives and studies. Racism is also evident in the depiction of Jesus Christ, who traditionally is portrayed as 'white' in Christian art, although he must be read biblically as a Person of Color (PoC). Examples such as the “Wales Window for Alabama” (1964) by Ronald John Petts and the contemporary icon by Kelly Latimore “Christ in The Rubble” (2023) show Jesus as PoC and address racism and social justice. Children’s Bibles continue to be dominated by ‘white’ depictions of Jesus and the people around him. Works such as the chil- dren’s Bibles by Desmond Tutu (lyrics) / Laure Fournier et al. (illustration) (2010), Sören Dalevi (lyrics) / Marcus-Gunnar Petterson (illustration) (2022), Willemijn de Weerd (lyrics) / Marieke ten Berge (illustration) (2022) and Andrea Karimé (lyrics) / Anna Lisicki-Hehn (illustration) (2023) of- fer more diverse and racism-sensitive depictions that contribute to the promotion of diversity competence and positive identity formation. The article argues for a more extensive representa- tion of diversity in depictions of Jesus Christ in Christian art and children’s Bibles in order to avoid discriminatory stereotypes and to encourage PoC, children and adults.

Aktuelle pädagogische und hermeneutische Ansätze aus Judentum, Christentum und Islam in Kindertora, Kinderbibel und Kinderkoran: Identitätsbildung, diversitätssensible Religionspädagogik und normative Diskurse - Keuchen, Marion (TheoWeb. Zeitschrift für Religionspädagogik)
Dieser Beitrag untersucht aktuelle pädagogische und hermeneutische Ansätze der jüdischen, christlichen und muslimischen Religionspädagogik in Kindertora, Kinderbibel und Kinderkoran. Er betont die Notwendigkeit für Lehrkräfte, sich mit den spezifischen pädagogischen und hermeneutischen Ansätzen der drei monotheistischen Religionen vertraut zu machen, um die didaktischen Heiligen Schriften im Unterricht angemessen nutzen zu können. Beispiele aus dem aktuellen Religionsunterricht zeigen Missverständnisse und Überraschungen auf, die durch unzureichendes Wissen entstehen. Der Artikel hebt die Bedeutung einer jüdischen Identitätsbildung, einer christlichen diversitätssensiblen Perspektive und von muslimischen normativen Diskursen in den verschiedenen Religionspädagogiken hervor und diskutiert die Herausforderungen und Chancen, die mit der Nutzung didaktisierter Heiliger Schriften verbunden sind.
Keywords: Heilige Schriften; interreligiöses Lernen; Schrifthermeneutik; Identität; diversitätssensible Religionspädagogik; jüdische Religionspädagogik; muslimische Religionspädagogik; christliche Religionspädagogik; Holy scriptures; interreligious learning; hermeneutics of scripture; identity; diversity-sensitive religious education; Jewish religious education; Muslim religious education; Christian religious education